Abundance estimation of Adélie penguins at the Esperanza/Hope Bay mega colony - Santos, Maria Mercedes; Hinke, Jefferson T.; Coria, Néstor Rubén; Fusaro, Bruno; Silvestro, Anahí Mariel; Juares, Mariana Alejandra (Polar Biology)
The Adélie penguin (Pygoscelis adeliae) breeding population at Esperanza/Hope Bay, at the tip of the Antarctic Peninsula, is one of the largest Adélie penguin colonies in Antarctica. Nevertheless, the last known published field count during the egg-laying period is from 1985/1986. We counted breeding pairs within the entire colony, consisting of 274 breeding groups, during the 2012/2013 breeding season for comparison with previously published ground and satellite-derived counts. We also counted breeding pairs in 26 breeding groups that have been monitored annually since 1995/1996. We estimated the current population size to be 104,139 (95th-percentile CI 70,126–138,151) breeding pairs for the whole colony. The counts indicate population declines of 15.9% over 27 years in the whole colony and 37.5% over 18 years in the annually monitored subset of breeding groups, respectively. The observed decrease matches recent trends reported in other Adélie penguin colonies throughout the western Antarctic Peninsula and southern Scotia Sea. This population assessment contributes to the current estimates of the total predator populations in the region, which is necessary information for the management of marine living resources. Fil: Santos, Maria Mercedes. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Hinke, Jefferson T. National Oceanic and Atmospheric Administration; Estados Unidos Fil: Coria, Néstor Rubén. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Fusaro, Bruno. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de ...